Effect of Fluorescent Pseudomonad Fluorescent Producing Indole Acetic Acid (IAA) Against Germination Red Chili (Capsicum annuum L.) - Aditya Willy Putra; Linda Advinda (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2022)
Red chili (Capsicum annuum L.) is an important horticultural commodity in Indonesia. Red chili propagation can be done by seed. Giving biological agents to seeds can accelerate the germination process. One of the biological agents capable of accelerating germination is fluorescent pseudomonad. Several species of pseudomonads are biological agents that can produce Indole Acetic Acid (IAA). This hormone plays a role in accelerating plant growth and development. The aim of this study was to examine the effect of fluorescent pseudomonads producing Indole Acetic Acid (IAA) on the germination of red chili (Capsicum annuum L.). This research is descriptive research and experimentation. The study design used was a complete randomized design (CRD) with 6 treatments (pf1, pf5, pf8, pf9 and pf10 isolates, and a aquades) and 3 repeats. The results showed that all the fluorescent pseudomonad isolates were able to produce IAA. The application of fluorescent pseudomonads did not significantly differ on germination, but significantly different on root length and stem length.